FAULT LOCALIZATION RISK MODELING IN COMMUNICATION NETWORKS - K.Sashi Rekha (International Journal of Advanced Science and Technology, 2020)
Over the past few decades, the Internet has become an integral component of our lives, being used the world over for a slew of purposes. This paper underscores the significance of Internet Service Provider (ISP) backbone networks and changing technology. They have outpaced the introduction of associated fault monitoring methodologies that are built and based on today’s IP protocols and routers. They also cause problems like loss of connectivity, router failures, and link faults. The failure of a component can lead to network disruption and degradation. Operational backbone networks are intrinsically exposed to a wide variety of faults and impairments. The networks are large, geographically distributed, and constantly evolving with complex hardware components and software. The task of fault localization and fault management is to detect, localize, and ultimately correct any condition that degrades network performance. These are vital for the continuous working, without disruption, of network components.They play a key role in enhancing system performance in a wide range of application domains. Dealing with fault localization thatof identifying shared failures is, in general, a Non-deterministic Polynomial (NP) time-hard problem.The complexity of theproblem increases whenthe application is executed on a Heterogeneous Distributed System (HDS), as both the computational nodes and the underlyingnetworks connecting them are heterogeneous. So the greedy approximation approach can find an approximate solution to resolve this problem(RamanaRaoKompellaet al. 2010).